Mission : impossible II [videorecording (DVD)] - Woo, John, 1948-; Cruise, Tom, 1962-; Cruise, Tom, 1962-; Scott, Dougray, 1965-; Newton, Thandiwe, 1972-; Rhames, Ving, 1961- (Widescreen DVD collection., 2000)
IMF agent Ethan Hunt partners up with Nyah Hall to stop renegade agent Sean Ambrose from releasing a new kind of terror on an unsuspecting world.